Inhibition of Fibrinoid Deposition by Heparin - Gilson, Saul B. (Thrombosis and Haemostasis, 1961)
Experimental glomerulitis in rabbits following intravenous injection of gamma globulin was inhibited by heparinization. The physiological and patho-physiological significance of this observation is considered.